PENGARUH PEMBERIAN JUS BAYAM HIJAU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI KLINIK PRATAMA CITRA MARENDAL KEC. DELI TUA KAB. DELI SERDANG TAHUN 2023 - Ariescha, Putri Ayu Yessy; Amanda, Cindy Aulia (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2023)
Anemia in pregnant ladies is an indirect cause of maternal mortality in Indonesia. The effects of anemia in pregnant women are: miscarriage, extended transport, mom and baby infections, haemorrhage, untimely birth, low start weight, malnutrition of the fetus, intrauterine increase retardation (IUGR). Non-pharmacological methods, specifically the consumption of green amaranth (Amaranthus Viridis), are used in interventions to growth hemoglobin degrees. This observe turned into carried out at Citra Marendal number one faculty from February to June 2023. This sort of study is a pre-submit-trial organization trial. The population recognized in this look at was pregnant girls with anemia. The cutting-edge pattern length is sixteen individuals selected at random from the population. The p-price acquired was (0.000) due to a -variable evaluation of the effect of green spinach juice on increasing hemoglobin tiers in anemic pregnant girls. therefore, from the outcomes of two-variable analysis with p < α (0.05), it can be concluded that spinach juice has the impact of growing hemoglobin in pregnant ladies at Citra Marendal Pratama health facility, Deli Tua District, Deli Serdang regent. girls with anemia with the aid of 2023. it's far recommended that expectant moms could advantage more from non-pharmacological interventions together with often consuming spinach juice to boom hemoglobin stages.